Strategy for Securing TNI Information Systems to Face Global Challenges in The Future - Dimas, Dimas; Pujiati, Herni (Dinasti International Journal of Management Science, 2025)
The current and future situation and conditions of scientific and technological development have raised the nature of threats to the national defense system. TNI seeks to face all kinds of threats, challenges, obstacles and disturbances that arise against national defense. Pusinfolahta TNI is tasked with preparing information and carrying out data processing on the use of TNI forces in the fields of administration and operations, organizing information technology support and securing information systems. The approach used in this research is a qualitative research method with descriptive analysis method. The results of the study recommend that a TNI Information System Security Strategy is needed in order to face the Global Challenge, through several innovative ideas including training and fostering human resources in the IT field, developing modern technology infrastructure and forming a monitoring team and strengthening TNI information system security. It is expected to support the main task of Pusinfolahta TNI in creating a TNI information system security strategy in facing the Global Challenge both now and in the future.